Strokes in children under the age of five - Rosińczuk-Tonderys, Joanna; Żerkowska, Urszula; Uchmanowicz, Izabela; Kalisz, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2011)
Introduction . Ischemic and hemorrhagic stroke occurs in children’s population with frequency 2.5/100,000/year, so more often than brain neoplastic tumors. Relatively often are strokes in neonatal period as well as prenatal — in fetal period (since 14th week) or maternal factors can be the reasons. The aim of the study . The aim of the study was introduction of stroke reasons, paying special attention to risk factors from the mother’s side, discussing accepted methods of rehabilitation and psychomotor improvement of children. Material and methods . The research was conducted at the Newborn Pathology Department and Children’s Neurology Department in the Specialist Hospital of Pediatric Diseases in Wroclaw from October 2007 to March 2008. The research study was based on a questionnaire for children’s mothers, in whom stroke was stated after labour. Results . From the research analysis results that in 70% of examined children hemorrhagic stroke was stated, whereas ischemic in 30%. Factors predisposing to occurrence of stroke in children were bad health state of mother during pregnancy and systematic using medicines by pregnant mothers, smoking and diet. The biggest number of labours took place before appointed time, also over half of examined children with diagnosed stroke was born by caesarean section. In most of the examined children after stroke eye disorders and epilepsy were present. Conclusions . The Vojta’s method was the most common method used in rehabilitation of children after stroke, over half of the children used adjunct therapies. Nursing Topics 2011; 19 (1): 13–20